Criminal Liability Policy Of Persons With Mental Disorders In Case Spreading Racial Issues - Alexandra Florecita Adja Mossa (Faculty of Law, Universitas Lampung, 2022)
Freedom of expression is stated in Article 28E of the 1945 Constitution. However, law enforcement obeys laws and norms that do not use the law as a source of law. This paper uses normative legal research method consisting of case approach and a statutory approach. Sources of data used are primary data obtained from interviews and secondary data obtained by collecting data contained in books, papers, journals, and print or electronic media. Laws and regulations relating to the existing problems are studied and analyzed, these are also legal materials. The data that has been obtained is then analyzed. The data analysis used is qualitative. Based on the results of research and discussion in the case, decision Number: 8/Pid.Sus/2019/PN.Srg, the judge decided that the defendant was legally and convincingly proven guilty and was threatened with a criminal sentence in Article 28 paragraph (2) in conjunction with Article 45A paragraph (2) Act. Law Number 19 of 2016 concerning Amendments to Law Number 11 of 2008 concerning Information and Electronic Transactions, Law Number 8 of 1981 concerning the Criminal Procedure Code and other relevant laws and regulations. Criminal liability for defendants with mental disorders in Article 44 of the Criminal Code which stipulates if the criminal acts committed by the perpetrator cannot be held accountable due to a mental disability during growth or mental disorders where by his mind or soul is disturbed due to diseases such as mental disorders, psychosis etc. The defendant's condition is that the defendant is not legally competent, as referred to in Article 32 of Law no. 8 of 2016 regarding disability, and there is no sense of justice for the perpetrators.